Quantization of Free Scalar Fields in the Presence of Natural Cutoffs - K. Nozari; F. Moafi; F. Rezaee Balef (Advances in High Energy Physics)
We construct a quantum theory of free scalar fields in (1+1)-dimensions based on the deformed Heisenberg algebra x^,p^=iħ1-βp+2β2p2, that admits the existence of both a minimal measurable length and a maximal momentum, where β is a deformation parameter. We consider both canonical and path integral formalisms of the scenario. Finally a higher dimensional extension is easily performed in the path integral formalism.